Osteoblastoma mandibular agresivo: tratamiento quirúrgico y rehabilitación con implantes - José Radi-Londoño; Fabio Becerra-Santos; Yolanda Mosquera-Silva; Norman Otálvaro-Rios (Universidad de Antioquia, 2000)
This report presents a case 01an 18year old male with an osteoblastoma in his right mandibular body, treated surgically with a block resection 01 the tumor. One year alter the procedure. a radiographic regeneration 01abone was observed, (Spontaneous osteogenesis) between the residual Iragments, having 70% 01 the height but with an inadequate width. With a reconstructive intention, the bone width was increased with autologous gralts taken Irom the symphisis area and alloplastic gralts on the new bone. This was done to allow the insertion 01osseointegrated implants and a rehabilitation with a lull bone anchored prostheses three years later. In a six year lollow-up the tumor has not relapsed and the implants show an adequate osseointegration.